2012
DOI: 10.1111/j.1439-0272.2012.01337.x
|View full text |Cite
|
Sign up to set email alerts
|

Sperm selection based on motility in polyvinylpyrrolidone is associated with successful pregnancy and embryo development

Abstract: The aim of this study was to investigate whether spermatozoon motility in polyvinylpyrrolidone (PVP) is associated with better embryo development and pregnancy rates in ICSI cycles. A total of 123 primary ICSI treatment cycles were included in this study. Semen samples were tested for motility before ICSI procedure in PVP. Within 3 min, the presence or absence of motility was recorded. Sperm functions were examined by the aniline blue (AB) chromatin condensation test and the hypoosmotic swelling test, and the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 45 publications
0
2
0
Order By: Relevance
“…The viscous layer is made of Poly Vinile Pyrolidin and Carboxymethylcellulose with different ratios. Previous studies revealed these compounds have a little destructive effect on sperm structure (Ahmad et al, 2003; Irez et al, 2013). The volumetric mass of this viscous layer is lower than semen and more than the sperm culture medium and is placed between the two layers (1.02 g/ml).…”
Section: Methodsmentioning
confidence: 97%
“…The viscous layer is made of Poly Vinile Pyrolidin and Carboxymethylcellulose with different ratios. Previous studies revealed these compounds have a little destructive effect on sperm structure (Ahmad et al, 2003; Irez et al, 2013). The volumetric mass of this viscous layer is lower than semen and more than the sperm culture medium and is placed between the two layers (1.02 g/ml).…”
Section: Methodsmentioning
confidence: 97%
“…Sperm quality, including both motility and morphology, is a crucial factor in achieving fertilization and successful pregnancy [5]. Studies have shown that a high rate of sperm motility and normal sperm morphology in a given sample positively correlate with fertilization and pregnancy rates during ICSI [6,7]. Sperm selection during ICSI typically involves an evaluation of sperm shape, size and structure as well as motility parameters under low (X20) magnification.…”
Section: Introductionmentioning
confidence: 99%